Evaluation of the Disability Determination Process for Traumatic Brain Injury in Veterans - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The Veterans Benefits Administration (VBA) provides disability compensation to veterans with a service-connected injury, and to receive disability compensation from the Department of Veterans Affairs (VA), a veteran must submit a claim or have a claim submitted on his or her behalf. Evaluation of the Disability Determination Process for Traumatic Brain Injury in Veterans reviews the process by which the VA assesses impairments resulting from traumatic brain injury for purposes of awarding disability compensation. This report also provides recommendations for legislative or administrative action for improving the adjudication of veterans' claims seeking entitlement to compensation for all impairments arising from a traumatic brain injury.
Keywords: Health and Medicine

Metrics for Successful Supercritical Water Oxidation System Operation at the Blue Grass Chemical Agent Destruction Pilot Plant - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The supercritical water oxidation system at the Blue Grass Chemical Agent Destruction Pilot Plant near Richmond, Kentucky is a secondary waste processing reactor that is an important unit in the overall function of the Blue Grass Chemical Agent Pilot Program. This system is designed to reactively destroy the primary products of agent hydrolysis, thus preventing chemical reformation of the original agents. This letter report develops metrics that can be used to determine the success or risks of failure of the system, focusing on safety, corrosion, performance, and reliability, availability, and maintainability.
Keywords: Conflict and Security Issues

Facilities Staffing Requirements for the Veterans Health Administration–Engineering Administration: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The National Academies of Sciences, Engineering, and Medicine convened a workshop on March 5-6, 2019, to explore staffing considerations for engineering administration at the Veterans Health Administration (VHA) of the U.S. Department of Veterans Affairs (VA). Workshop speakers shared information about (1) data and data management, (2) contracting strategies, and (3) perspectives on challenges and expectations at various VHA facilities. This Proceedings of a Workshop—in Brief summarizes the presentations and discussions that took place during the workshop.
Keywords: Behavioral and Social Sciences; Health and Medicine

Performance Management and Financing of Facility Engineering Programs at the Veterans Health Administration: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The National Academies of Sciences, Engineering, and Medicine convened a workshop on May 8-9, 2019, to gather data on performance management and financing associated with the complex and diverse physical plants that support a wide variety of Veterans Health Administration (VHA) facilities. This workshop was the fourth in a series undertaken to assist the larger effort by an ad hoc committee of the National Academies for the Veterans Administration to prepare a resource planning and staffing methodology guidebook for VHA Facility Management (Engineering) Programs. This publication summarizes the presentations and discussions from the workshop.
Keywords: Behavioral and Social Sciences

Facilities Staffing Requirements for the Veterans Health Administration–Resourcing, Workforce Modeling, and Staffing: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
In January 2019, the National Academies of Sciences, Engineering, and Medicine convened the 2-day Workshop on Resourcing, Workforce Modeling, and Staffing. This workshop is one of several data-gathering sessions to support the committee's iterative study. The overarching goal of the study is to help the Veterans Health Administration (VHA) assess the overall resource needs of its Facilities Management Program and to develop budget and staffing methodologies. Such methodologies can provide better justification for ensuring that local VHA programs are adequately and consistently staffed to accomplish the mission and meet all requirements. This publication summarizes the presentations and discussions from the workshop.
Keywords: Behavioral and Social Sciences; Health and Medicine

Facilities Staffing Requirements for the Veterans Health Administration–Capital Asset Inventory Database Management and Strategic Capital: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The National Academies of Sciences, Engineering, and Medicine convened a workshop on February 19-20, 2019. The purpose of this 2-day workshop was to explore the tools, techniques, and models being used by the Veterans Health Administration (VHA) and other organizations both within and outside the federal government for facilities asset and data management, capital planning, and project management relevant to Veterans Affairs (VA) hospitals, and in particular the staffing challenges relative to those functions. This publication summarizes the presentations and discussions from the workshop.
Keywords: Behavioral and Social Sciences

Facilities Staffing Requirements for the Veterans Health Administration–Operations and Maintenance of the Physical Plant and Equipment: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On February 5-6, 2019 the National Academies of Sciences, Engineering, and Medicine convened a workshop to discuss current information and future research possibilities that could inform the continued effort to develop a resource planning and staffing methodology guidebook for Veterans Health Administration Facility Management (Engineering) Programs. Discussions focused on the impacts of plant operations and maintenance (O&M) on patient care and outcomes, measuring O&M effectiveness, cost management, regulatory and accreditation requirements impacting plant O&M, O&M staff competencies, and customer-service feedback. This publication summarizes the presentations and discussions from the workshop.
Keywords: Behavioral and Social Sciences; Health and Medicine

Facilities Staffing Requirements for the Veterans Health Administration—Resource Planning and Methodology for the Future: Interim Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The National Academies of Sciences, Engineering, and Medicine was tasked by the Veterans Health Administration (VHA) to prepare a comprehensive resource planning and staffing methodology guidebook for VHA Facility Management (Engineering) Programs. The resource and staffing methodology must take into account all significant parameters and variables involved in the VHA Engineering Programs. The methodology should yield customized outputs based on site-specific input data, to enable specification of the optimal budget and staffing levels for each site.
Keywords: Behavioral and Social Sciences

Climate Change and Ecosystems - National Academy of Sciences (The National Academies Press, 2019)
The National Academies convened a forum on November 8-9, 2018 to highlight current research frontiers such as the effects of climate extremes, interactions among climate and other stressors, the timing, sequence, and clustering of climate-related events, and tipping points for abrupt change. Topics of discussion at the forum pertained to the changes ecosystems are currently undergoing, sustaining ecosystems, the impact of ecosystems on global climate change, societal adaptation to climate change, and priorities for future research. This report summarizes the presentations and discussions from the forum.
Keywords: Environment and Environmental Studies

21st Century Paradigm Change in Performance and Design Metrics: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
In September 2015, the National Academies of Sciences, Engineering, and Medicine convened a two-day workshop on evolving paradigms for design and manufacturing. Participants discussed ways to lower costs and shorten production time in defense systems while bringing materials and manufacturing alternatives into the tradespace. This publication summarizes the presentations and discussions from the workshop.
Keywords: Conflict and Security Issues

Improving Care to Prevent Suicide Among People with Serious Mental Illness: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Suicide prevention initiatives are part of much broader systems connected to activities such as the diagnosis of mental illness, the recognition of clinical risk, improving access to care, and coordinating with a broad range of outside agencies and entities around both prevention and public health efforts. Yet suicide is also an intensely personal issue that continues to be surrounded by stigma. On September 11-12, 2018, the National Academies of Sciences, Engineering, and Medicine held a workshop in Washington, DC, to discuss preventing suicide among people with serious mental illness. The workshop was designed to illustrate and discuss what is known, what is currently being done, and what needs to be done to identify and reduce suicide risk. Improving Care to Prevent Suicide Among People with Serious Mental Illness summarizes presentations and discussions of the workshop.
Keywords: Health and Medicine; Behavioral and Social Sciences

Estimating the Prevalence of Human Trafficking in the United States: Considerations and Complexities: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
A 2-day public workshop on estimating the prevalence of human trafficking in the United States was held by the Committee on National Statistics in collaboration with the Committee on Population April 8-9, 2019. The workshop explored current and innovative sampling methods, technological approaches, and analytical strategies for estimating the prevalence of sex and labor trafficking in vulnerable populations. The workshop, sponsored by the Office on Women's Health at the Department of Health and Human Services (HHS), brought together statisticians, survey methodologists, researchers, public health practitioners, and other experts who work closely with human trafficking data or with the survivors of trafficking. Participants addressed the current state of research on human trafficking, advancements in data collection, and gaps in the data. They discussed international practices and global trends in human trafficking prevalence estimation and considered ways in which collaborations across agencies and among the U.S. government and private-sector organizations have advanced counter-trafficking efforts. The workshop highlighted the importance of understanding the scope of human trafficking in order to inform and receive support from policy makers and change agents.
Keywords: Behavioral and Social Sciences

An Approach to Evaluate the Effects of Concomitant Prescribing of Opioids and Benzodiazepines on Veteran Deaths and Suicides - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Opioid prescriptions for acute and chronic pain increased dramatically from the late 1990s into the current decade in both the civilian and the Department of Veterans Affairs and Department of Defense treatment environments. Similarly, prescriptions for benzodiazepines also increased significantly for anxiety and insomnia. Combinations of opioid and benzodiazepines have proven fatal when taken concurrently, with research demonstrating this phenomenon for nearly 40 years. This issue is exacerbated within the veteran population because of higher rates of pain, anxiety and other related health issues due to military life. An evaluation of the relationship between opioid and benzodiazepine medication practices at the VA is necessary to improve treatment for mental health and combat-related trauma for veterans.
Keywords: Health and Medicine

Key Operational Characteristics and Functionalities of a State-of-the-Art Patient Scheduling System: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Current electronic health care systems are archaic and face similar challenges that limit efficient patient scheduling and health care accessibility. A large initiative to improve these systems is underway because these challenges exist across many electronic health care systems. However, these challenges are exacerbated within the Department of Veterans Affairs (VA) Healthcare System due to uniquely complex aspects of that system and its patients. The National Academies convened a two-day workshop to explore important operational characteristics and functionalities of effective patient scheduling systems. This workshop built upon a 2015 Institute of Medicine report that identified hurdles to timely patient scheduling specifically within the Veterans Health Administration, who administers the VA system. Discussions at the workshop reviewed past healthcare system patient, clinician, and scheduler experiences and technologies. They also highlighted the importance of design, implementation, and adaptability of scheduling systems. This publication summarizes the presentations from the workshop.
Keywords: Health and Medicine; Computers and Information Technology

Review of DOD's Approach to Deriving an Occupational Exposure Level for Trichloroethylene - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Trichloroethylene (TCE) is a solvent that is used as a degreasing agent, a chemical intermediate in refrigerant manufacture, and a component of spot removers and adhesives. It is produced in mass quantities but creates dangerous vapors and is an environmental contaminant at many industrial and government facilities, including facilities run by the U.S. Department of Defense (DoD). It is important to determine the safe occupational exposure level (OEL) for the solvent in order to protect the health of workers who are exposed to its vapors. However, there are concerns that the current occupational standards insufficiently protect workers from these health threats.
Keywords: Environment and Environmental Studies

Climate Resilience and Benefit–Cost Analysis: A Handbook for Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB’s Airport Cooperative Research Program (ACRP) Research Report 199: Climate Resilience and Benefit–Cost Analysis: A Handbook for Airports provides information on how to apply benefit–cost analysis tools and techniques to improve decision making affecting resilience of airport infrastructure projects in response to potential long-term impacts of climate change and extreme weather events.The handbook is designed to improve the process by which infrastructure investment strategies are evaluated, with an emphasis on ensuring climate-related resiliency.Procedures for presenting assumptions and results transparently and for implementing the process are also included so that industry users and decision makers can understand and communicate the outcome of the analytical process.Based on data availability, the analytical methods included in the handbook focus on two specific areas of climate change likely to affect airports (although these methods can, in principle, be used more widely): (1) the potential for extreme flooding events resulting from storm surge and sea level rise near coastal airports, and (2) the potential for rising temperatures that require weight restrictions on aircraft takeoffs (or possibly full flight delays) at airports with shorter runways in warm climates or at high elevations.The results available from application of the suggested methodologies do not necessarily make the decision of whether to invest in a mitigation project to combat climate change any easier but, rather, provide a full range of potential outcomes and possibilities for airport planners and managers to consider. Using this methodology, airport decision makers can then determine how much risk from uncertain climate change and extreme weather events they are willing or able to accommodate. Implementation of the methods presented in the handbook can be used to obtain essential quantifiable estimates of those risks, which is of particular value to airport financial professionals.The handbook is accompanied by a set of Microsoft Excel models to support the decision-making process (one for extreme water rise causing potential flooding events, and the other for high temperatures that may affect weight restrictions on aircraft takeoffs), a video tutorial, a report summary document, and an executive briefing to help decision makers understand the process.
Keywords: Transportation and Infrastructure

A Research Review of Interventions to Increase the Persistence and Resilience of Coral Reefs - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Coral reef declines have been recorded for all major tropical ocean basins since the 1980s, averaging approximately 30-50% reductions in reef cover globally. These losses are a result of numerous problems, including habitat destruction, pollution, overfishing, disease, and climate change. Greenhouse gas emissions and the associated increases in ocean temperature and carbon dioxide (CO2) concentrations have been implicated in increased reports of coral bleaching, disease outbreaks, and ocean acidification (OA). For the hundreds of millions of people who depend on reefs for food or livelihoods, the thousands of communities that depend on reefs for wave protection, the people whose cultural practices are tied to reef resources, and the many economies that depend on reefs for fisheries or tourism, the health and maintenance of this major global ecosystem is crucial.
Keywords: Earth Sciences

Advancing Progress in the Development of Combination Cancer Therapies with Immune Checkpoint Inhibitors: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
In recent years, significant progress has been made in the clinical development and use of various types of cancer immunotherapy, all of which rely on the immune system to fight cancer. The majority of new cancer drug applications submitted to the Food and Drug Administration (FDA) are for immunotherapies or combinations involving immunotherapies. One type of immunotherapy is an immune checkpoint inhibitor. Cells in the human body have proteins that regulate the immune system response to foreign invaders (e.g., cancer cells, microorganisms). However, cancer cells can coopt these "checkpoint" proteins and thwart the immune system's ability to recognize and attack cancer cells. To help promote an immune response to cancer, researchers have developed immune checkpoint inhibitors that enable T-cells to recognize cancer cells as foreign and to prevent deactivation of an immune system response.
Keywords: Health and Medicine

Forest Health and Biotechnology: Possibilities and Considerations - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The American chestnut, whitebark pine, and several species of ash in the eastern United States are just a few of the North American tree species that have been functionally lost or are in jeopardy of being lost due to outbreaks of pathogens and insect pests. New pressures in this century are putting even more trees at risk. Expanded human mobility and global trade are providing pathways for the introduction of nonnative pests for which native tree species may lack resistance. At the same time, climate change is extending the geographic range of both native and nonnative pest species. Biotechnology has the potential to help mitigate threats to North American forests from insects and pathogens through the introduction of pest-resistant traits to forest trees. However, challenges remain: the genetic mechanisms that underlie trees' resistance to pests are poorly understood; the complexity of tree genomes makes incorporating genetic changes a slow and difficult task; and there is a lack of information on the effects of releasing new genotypes into the environment. Forest Health and Biotechnology examines the potential use of biotechnology for mitigating threats to forest tree health and identifies the ecological, economic, and social implications of deploying biotechnology in forests. This report also develops a research agenda to address knowledge gaps about the application of the technology.
Keywords: Environment and Environmental Studies; Biology and Life Sciences

Reusable Elastomeric Respirators in Health Care: Considerations for Routine and Surge Use - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Protecting the health and safety of health care workers is vital to the health of each of us. Preparing for and responding to a future influenza pandemic or to a sustained outbreak of an airborne transmissible disease requires a high-level commitment to respiratory protection for health care workers across the wide range of settings in which they work and the jobs that they perform. Keeping health care workers healthy is an ethical commitment both in terms of addressing the occupational risks faced by health care workers and of providing for the continuity of patient care and services needed to maintain the health of individuals and communities. During a public health emergency, challenges will arise concerning the availability of respiratory protective devices (i.e., respirators). Reusable respirators (specifically, reusable half-facepiece elastomeric respirators) are the standard respiratory protection device used in many industries, and they provide an option for use in health care that has to date not been fully explored. The durability and reusability of elastomeric respirators make them desirable for stockpiling for emergencies, where the need for large volumes of respirators can be anticipated. However, they are used infrequently in health care. Reusable Elastomeric Respirators in Health Care explores the potential for the use of elastomeric respirators in the U.S. health care system with a focus on the economic, policy, and implementation challenges and opportunities. This report examines the practicability of elastomeric use in health care on a routine basis and during an influenza pandemic or other large aerosol-transmissible outbreak, when demand for respiratory protective devices by U.S. health care personnel may be larger than domestic supplies. The report also addresses the issues regarding emergency stockpile management of elastomeric respiratory protective devices.
Keywords: Health and Medicine